Hepatitis C virus surveillance and identification of human pegivirus 2 in a large Cameroonian cohort. Issue 1 (3rd October 2018) - Rodgers, Mary A.; Holzmayer, Vera; Vallari, Ana; Olivo, Ana; Forberg, Kenn; Fuhrman, Jill; Coller, Kelly E.; Awazi, Bih; Kenmegne Sidje, Jules Bertrand; Frankel, Matthew B.; Berg, Michael G.; Mbanya, Dora; et al.
Summary: The prevalence of chronic hepatitis C virus (HCV) and the presence of human pegivirus 2 (HPgV‐2) have not been examined in Cameroon, although HCV has been associated with HPgV‐2 infections previously. Herein we aimed to characterize the burden and genetic diversity of HCV and the presence of HPgV‐2 in Cameroon. Retrospective plasma specimens collected from N = 12 369 consenting subjects in South Cameroon from 2013 to 2016 were included in the study. The majority (97.1%) of participants were patients seeking health care. All specimens were screened for HCV using the Abbott RealTi m e HCV viral load assay and positive specimens with remaining volume were also screened for HPgV‐2 antibodies on the Abbott ARCHITECT instrument, followed by molecular characterization. Overall, HCV RNA was detected in 305 (2.47%; 95% CI: 2.21%‐2.75%) specimens. Notably, the prevalence of HCV RNA was 9.09% amongst participants over age 40 and 3.81% amongst males. Phylogenetic classification of N = 103 HCV sequences identified genotypes 1 (19.4%), 2 (15.5%) and 4 (65.1%) within the study cohort. Amongst HCV RNA‐positive specimens, N = 28 (10.6%; 95% CI: 7.44%‐14.90%) specimens also had detectable HPgV‐2 antibodies. Of these, N = 2 viremic HPgV‐2 infections were confirmed by sequencing and shared 93‐94 median % identity with strains found on other continents. This is the first study to determine the prevalence of chronic HCV in Cameroon, and the discovery of HPgV‐2 in this study cohort expands the geography of HPgV‐2 to the African continent, indicating a widespread distribution exists.